Fever of unknown origin in the dog - PARDALI (Δ. ΠΑΡΔΑΛΗ), D.; ADAMAMA-MORAITOU (Κ. ΑΔΑΜΑΜΑ-ΜΩΡΑΪΤΟY), K.; RALLIS (Τ. ΡΑΛΛΗΣ), T. (Journal of the Hellenic Veterinary Medical Society, 2017)
Fever of unknown origin (FUO) refers to a febrile syndrome that does not resolve spontaneously in an adequate period of time for the remission of self-limited infections and definitive diagnosis cannot be established despite considerable diagnostic effort. This definition is an extrapolation from human medicine, since FUO has not been still defined accurately in animals. The spectrum of diseases involved in FUO includes infectious, neoplastic, immune-mediated, miscellaneous and not defined diseases. Clients and clinicians must be aware that FUO may be a diagnostic challenge. The diagnostic plan should always begin with costless and simple tests followed by more invasive and expensive procedures. The initial diagnostic approach of FUO includes a detailed history, a thorough physical examination, a routine laboratory evaluation and radiographical examination of the thorax and abdomen. If diagnosis cannot be achieved, specific non-invasive tests should then be applied. No therapeutic trial should be initiated during evaluation, since it may alleviate clinical symptoms and alter the laboratory results potentially misleading the diagnostic approach. Nevertheless, fever is rarely harmful. In body temperature above 41,0 °C, diagnostic evaluation is postponed and the initiation of an emergency therapy is strongly recommended. If definitive diagnosis is confirmed, the dog is treated accordingly. Therapeutic trial is indicated, if despite the thorough evaluation no diagnosis is established or the owners are unwilling to support the cost of the diagnostic work-up of their dog. Therapy is focused on the administration of antibiotics followed by steroids and finally non-steroid anti-inflammatory drugs.